Voice and voices in antiquity - Slater, Niall W., 1954- (Mnemosyne, Supplements, 2016)
Voice and Voices in Antiquity draws together 18 studies of the changing concept of voice and voices in the oral traditions and subsequent literate genres of the ancient world. Ranging from the poet's voice to those of characters as well as historically embodied communities, and from the interface between the Greek and Near Eastern worlds to the western reaches of the Roman Empire, the scholars assembled here offer a methodologically rich and diverse series of approaches to locating the power of voice as both poetic construct and communal memory. The results not only enrich our understanding of the strategies of epic, lyric, and dramatic voices but also illuminate the rhetorical claims given voice by historians, orators, philosophers, and novelists in the ancient world.